Substitution mechanism of Ga for Zn site depending on deposition temperature for transparent conducting oxides - Lee, Deuk-Hee; Kim, Kyoungwon; Chun, Yoon Soo; Kim, Sangsig; Lee, Sang Yeol (Current applied physics, 2012)
High quality transparent conductive gallium-doped zinc oxide (GZO) thin films were deposited on glass substrates using rf-magnetron sputtering system at the temperature ranging from room temperature (RT) to 500 °C. The temperature-dependence of Ga doping effect on the structural, optical and electrical properties in ZnO has been investigated. For the GZO thin films deposited at over 200 °C, (103) orientation was strongly observed by X-ray diffraction analysis, which is attributed to the substitution of Ga elements into Zn site. X-ray photoelectron spectroscopy measurements have confirmed that oxygen vacancies were generated at the temperature higher than 300 °C. This might be due to the effective substitution of Ga3+ for Zn site at higher temperature. It was also found that the optical band gap increases with deposition temperature. The optical transmittance of GZO thin films was above 87% in the visible region. The GZO thin films grown at 500 °C showed a low electrical resistivity of 4.50 × 10−4 Ω cm, a carrier concentration of 6.38 × 1020 cm−3 and a carrier mobility of 21.69 cm2/V. [Display omitted] ► High quality transparent conductive gallium-doped zinc oxide (GZO) thin films were deposited on quartz glass substrates using rf-magnetron sputtering system in the deposition temperature range of room temperature (RT) to 500 °C. ► The temperature-depedence of Ga doping effect on the structural, optical and electrical properties in ZnO has been investigated. ► X-ray photoelectron spectroscopy measurements on GZO thin films was confirmed that the oxygen vacancy was generated because Ga3+ was substituted for Zn site more actively at the deposition temperature of higher than 300 °C. ► The optical transmittance of GZO thin films was represented above 85% in the visible region. The GZO thin films formed at a deposition temperature of 500 °C showed a low electrical resistivity of 4.50 × 10−4 Ω cm, a carrier concentration of 6.38 × 1020 cm−3 and a carrier mobility of 21.69 cm2/V.